Preparation method and application of bismuth nanosheet material

Through the preparation of BI NSS materials BI NSS, the BI NSS catalyst is formed using the original electrical reduction method, which solves the inhibitory problem of electro -catalytic CO2 restoration of hydrogen gas analysis reactions, and realizes the efficient conversion of CO2 to metal acid. Suitable for industrialization.

CN119352103APending Publication Date: 2025-01-24GUANGZHOU UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411555933.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

During the electrocatalytic CO2 reduction process, how to suppress the precipitation reaction of hydrogen and improve the selectivity, activity and stability of CO2RR, especially at high current density.

Method used

By preparing the BI NSS of nano -sliced ​​materials, the front -drive BIOI in situ power reduction method is used to form a catalyst with high selectivity and running stable at high current density.

Benefits of technology

The efficient conversion of CO2 to metal acid has been achieved, and high -Fatraidi efficiency is maintained, suitable for industrialized applications, and the process of preparing is simple, controllable, green, and economical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352103A_ABST
    Figure CN119352103A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electrocatalytic CO2 reduction, and particularly provides a preparation method and application of a bismuth nanosheet material.The preparation method comprises the following steps that a carbon material is subjected to high-temperature calcination treatment and then serves as a substrate, a bismuth source is introduced to the substrate through an electrodeposition method, a precursor BiOI is prepared, an electrolyte is a mixed solution containing bismuth salt and iodized salt, and the bismuth nanosheet material is obtained; the pH range is adjusted to be 1-3; the precursor BiOI is reduced through an in-situ electroreduction method, and the bismuth nanosheet material Bi NSs is prepared. According to the invention, through in-situ conversion of BiOI, a Bi favorable crystal face is specifically formed, the formed composite material with excellent CO2 conversion capability can realize efficient conversion from CO2 to formate, and meanwhile, the formed material can operate under high current density and has industrial prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrocatalytic CO2 reduction, and in particular relates to a preparation method and application of a bismuth nanosheet material. Background Art

[0002] The storage of fossil energy is limited and the exploitation of fossil energy by humans is still intensifying, so human society is facing a severe energy crisis. Using fossil fuels as an energy supplier has also led to a sharp increase in CO2 emissions. Although the large amount of CO2 emitted in the air will lead to a series of environmental problems, CO2, as a cheap C1 raw material, can be converted into high-value-added fuels and chemicals through catalytic reactions, which not only makes a great contribution to my country's energy conservation and emission reduction, but also opens up a new fuel synthesis path. Among the many conversion technologies, CO2 electroreduction (CO2RR) technology has attracted widespread attention due to its mild conditions, controllable reaction, environmental friendliness and numerous products (formic acid, methanol, carbon monoxide, ethanol and ethylene, etc.). However, the electrocatalytic conversion of CO2 is often accompanied by a competing reaction - hydrogen evolution (HER). How to inhibit the hydrogen evolution reaction and make CO2RR have excellent selectivity, activity and stability are three factors that are emphasized in this field.

[0003] To improve the selectivity and activity of electrocatalysts, researchers have used various strategies, such as the use of nanostructures, defects, and selective face exposure. However, the actual active sites, stability, and reaction mechanisms under practical conditions remain controversial. Although other researchers have found that Bi-O interactions are crucial for the effectiveness of Bi-based electrocatalysts in the electrochemical CO2 reduction reaction, Pander et al. concluded that Bi is an oxide-independent electrocatalyst by observing the unchanged oxide layer on the Bi surface using in situ attenuated total reflection infrared spectroscopy. Related research results show that in the formation of HCOOH, the Bi(012) face and the Bi(110) face are very active and have good activity. In addition, it is reported that the use of layered metallic Bi electrocatalysts in CO2RR is an effective strategy because the layered structure can generally improve performance.

[0004] Chinese patent CN109939670B discloses a bismuth-based composite catalyst for CO2 electroreduction to formic acid and its preparation method. This patent improves acid resistance and resistance to high-concentration formic acid inhibition while maintaining high formic acid selectivity, thereby improving chemical stability. However, there is still the problem of decreased Faraday efficiency when the current density is high.

[0005] Chinese patent CN109518222B discloses a bismuth-based catalyst for electrocatalytic reduction of CO2 to formic acid, its preparation method and application. The bismuth-based catalyst in this patent has higher specific surface area, abundant surface chemical reaction sites, specific exposed crystal faces, and diversified size effects, so it exhibits higher catalytic activity in the electrocatalytic CO2 reduction system. However, it still has the disadvantage of decreased Faraday efficiency when the current density is high. Summary of the invention

[0006] In view of the above-mentioned defects of the prior art, the object of the present invention is to provide a method for preparing bismuth nanosheet materials, wherein a catalyst having high selectivity and operating at a high current density is obtained by in-situ electroreduction of the precursor BiOI, which can be used for 100 mA cm -2 The above runs stably.

[0007] The present invention provides a method for preparing a bismuth nanosheet material, comprising the following steps:

[0008] (1) a carbon material is subjected to high temperature calcination treatment and used as a substrate, and a bismuth source is introduced onto the substrate by an electrodeposition method to prepare a precursor BiOI, wherein the electrolyte is a mixed solution containing a bismuth salt and an iodine salt, and the pH range is adjusted to 1-3;

[0009] (2) The precursor BiOI obtained in step (1) is reduced by an in-situ electro-reduction method to prepare bismuth nanosheet material Bi NSs.

[0010] Preferably, the carbon material in step (1) is carbon cloth, and the high temperature calcination treatment is calcination at 500-600° C. in a tubular furnace for 90-120 minutes.

[0011] Preferably, the bismuth salt in step (1) is Bi(NO3)3·5H2O, and the iodine salt is KI.

[0012] Preferably, in step (1), the concentration of bismuth salt in the electrolyte is 0.03-0.05 mol / L, the concentration of iodine salt is 0.3-0.5 mol / L, and the pH is adjusted to 1.5.

[0013] Preferably, the electrodeposition in step (1) is carried out at -0.385 V vs. RHE for 10-12 minutes.

[0014] Preferably, the electrolyte for electroreduction in step (2) is KHCO3 with a concentration range of 0.4-0.6 mol / L.

[0015] Preferably, the electroreduction in step (2) is carried out at -0.6 V vs. RHE for 3-5 minutes.

[0016] In a second aspect, the present invention also provides bismuth nanosheet material Bi NSs prepared by the above preparation method.

[0017] In a third aspect, the present invention also provides a bismuth nanosheet material prepared by the above preparation method at 100 mA cm -2 The above is an application of the selective conversion of CO2 into formate.

[0018] Different from the common preparation method, the present invention directly converts Bi-Bi from the combination of Bi and O through in-situ conversion of BiOI, specifically forms Bi-favorable crystal planes Bi(012) and Bi(110), and obtains a composite material with excellent CO2 conversion ability, which can realize the efficient conversion of CO2 to formate and can operate at high current density, and has good industrial prospects.

[0019] The beneficial effects of the present invention are:

[0020] 1) The bismuth nanosheet material Bi NSs prepared by the present invention has high selectivity for formate and can achieve excellent CO2 conversion;

[0021] 2) The bismuth nanosheet material Bi NSs prepared by the present invention can maintain a high Faraday efficiency at a high current density and has the potential for industrial application;

[0022] 3) The preparation process of the present invention is simple, controllable, green, economical, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the XRD pattern of the bismuth nanosheet material precursor BiOI prepared in Example 1 of the present invention;

[0024] Figure 2 This is an XPS graph of the bismuth nanosheet material precursor BiOI prepared in Example 1 of the present invention;

[0025] Figure 3 This is a SEM image of the bismuth nanosheet material Bi NSs prepared in Example 1 of the present invention;

[0026] Figure 4 This is a SEM image of the bismuth nanosheet material Bi NSs prepared in Example 2 of the present invention;

[0027] Figure 5 This is a SEM image of the bismuth nanosheet material Bi NSs prepared in Example 3 of the present invention;

[0028] Figure 6 This is an ex-situ XRD pattern of the bismuth nanosheet material Bi NSs prepared in Example 1 of the present invention;

[0029] Figure 7This is a Faraday efficiency diagram of the bismuth nanosheet material Bi NSs prepared in Example 1 of the present invention when tested in an H-type electrolytic cell;

[0030] Figure 8 This is a linear sweep voltammetry test curve of the bismuth nanosheet material Bi NSs prepared in Example 1 of the present invention;

[0031] Fig. 9 This is a total current density diagram of the bismuth nanosheet material Bi NSs prepared in Example 1 of the present invention;

[0032] Fig.10 This is a Faraday efficiency diagram of the bismuth nanosheet material Bi NSs prepared in Example 1 of the present invention tested in a flow electrolytic cell;

[0033] Fig.11 This is a formic acid current density diagram of the bismuth nanosheet material Bi NSs prepared in Example 1 of the present invention;

[0034] Fig.12 This is an energy efficiency diagram of the bismuth nanosheet material Bi NSs prepared in Example 1 of the present invention;

[0035] Fig.13 This is a stability test diagram of the bismuth nanosheet material Bi NSs prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] In order to more clearly illustrate the present invention and have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0037] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0038] The present invention is further described in conjunction with the following examples.

[0039] Embodiment 1:

[0040] One at 100mA cm -2 The above method for preparing the stably operating bismuth nanosheet Bi NSs material comprises the following specific steps:

[0041] 1) Cut to 1*2cm 2The hydrophilic carbon cloth of different sizes was used as the electrodeposition substrate and calcined at 600℃ in a tube furnace for 2 hours. 2mmol Bi(NO3)3·5H2O, 20mmol KI and 50mL deionized water were mixed, the pH was adjusted to 1.5 with nitric acid, and the precursor BiOI was obtained by electrodeposition at -0.385V vs. RHE for 10 minutes on the carbon cloth.

[0042] 2) The electroreduction conditions were then adjusted in 0.5 M KHCO3 at -0.6 V vs. RHE for 3 min to obtain BiNSs material.

[0043] Embodiment 2:

[0044] KI was changed to KBr, the substrate was changed to hydrophobic carbon cloth, and other preparation conditions remained unchanged.

[0045] 1) Cut to 1*2cm 2 The hydrophobic carbon cloth of different sizes was used as the electrodeposition substrate and calcined at 600°C in a tube furnace for 2 hours. 2mmol Bi(NO3)3·5H2O, 20mmol KBr and 50mL deionized water were mixed, the pH was adjusted to 1.5 with nitric acid, and the precursor BiOBr was obtained by electrodeposition at -0.385V vs. RHE for 10 minutes on the carbon cloth.

[0046] 2) The electroreduction conditions were then adjusted in 0.5 M KHCO3 at -0.6 V vs. RHE for 3 min to obtain BiNSs material.

[0047] Embodiment three:

[0048] KI was changed to KCl, the substrate was changed to hydrophobic carbon cloth, and other preparation conditions remained unchanged.

[0049] 1) Cut to 1*2cm 2 The hydrophobic carbon cloth of different sizes was used as the electrodeposition substrate and calcined at 600℃ in a tube furnace for 2 hours. 2mmol Bi(NO3)3·5H2O, 20mmol KCl and 50mL deionized water were mixed, the pH was adjusted to 1.5 with nitric acid, and the carbon cloth was electrodeposited at -0.385V vs. RHE for 10 minutes to obtain the precursor BiOCl.

[0050] 2) The electroreduction conditions were then adjusted in 0.5 M KHCO3 at -0.6 V vs. RHE for 3 min to obtain BiNSs material.

[0051] Embodiment 4

[0052] Compared with Example 1, the electroreduction conditions are changed.

[0053] 1) Cut to 1*2cm 2The hydrophilic carbon cloth of different sizes was used as the electrodeposition substrate and calcined at 600℃ in a tube furnace for 2 hours. 2mmol Bi(NO3)3·5H2O, 20mmol KI and 50mL deionized water were mixed, the pH was adjusted to 1.5 with nitric acid, and the precursor BiOI was obtained by electrodeposition at -0.385V vs. RHE for 10 minutes on the carbon cloth.

[0054] 2) Subsequently, the electroreduction conditions were adjusted in 1 M KHCO3 and electroreduction was performed at -0.9 V vs. RHE for 6 min to obtain Bi NSs material.

[0055] Embodiment 5

[0056] Compared with Example 1, the in-situ electroreduction method is replaced by other conventional methods.

[0057] 1) Cut to 1*2cm 2 The hydrophilic carbon cloth of different sizes was used as the electrodeposition substrate and calcined at 600℃ in a tube furnace for 2 hours. 2mmol Bi(NO3)3·5H2O, 20mmol KI and 50mL deionized water were mixed, the pH was adjusted to 1.5 with nitric acid, and the precursor BiOI was obtained by electrodeposition at -0.385V vs. RHE for 10 minutes on the carbon cloth.

[0058] 2) 10 mg of tannic acid and 0.75 mg of sodium borohydride were dissolved in 8 mL of deionized water, and then the carbon cloth containing the precursor was immersed and stirred at 25° C. for 7 min to obtain Bi NSs material.

[0059] Figure 1 and Figure 2 This is the XRD and XPS diagram of the precursor BiOI. Figure 3 This is the SEM image of Bi NSs material prepared by in-situ electroreduction. Figure 1 This indicates the successful synthesis of BiOI. Figure 2 The existence of trivalent Bi can be used to assist in explaining the existence of the material. Figure 3 It can be seen that the Bi NSs material sample prepared in Example 1 has regular size and shape.

[0060] Since different anions have an effect on the morphology of Bi NSs, such as Figure 4 As shown in the SEM image, the BiNSs material prepared in Example 2 exhibits an irregular particle morphology as a whole. Figure 5 As shown in the SEM image, the Bi NSs material prepared in Example 3 presents a loose nanosheet morphology as a whole.

[0061] Figure 6 This is the non-in-situ XRD pattern of the bismuth nanosheet Bi NSs material prepared in the preferred embodiment 1, showing the formation process of bismuth nanosheets Bi(012) and Bi(110).

[0062] In order to more clearly illustrate the content of the present invention, the present invention also carried out the following detection experiments:

[0063] Electrochemical performance test:

[0064] 1) Using an H-type electrolytic cell, in a 0.5 M KHCO3 solution, the Bi NSs material prepared in the preferred embodiment 1 was used as the cathode, Ag / AgCl was used as the reference electrode, and the Pt sheet was used as the counter electrode. Electrochemical testing was performed using a Chenhua electrochemical workstation in the voltage range of -0.7 to -0.9 V vs. RHE. The gas products were detected by gas chromatograph, and the liquid products were detected by nuclear magnetic resonance.

[0065] Figure 7 This is the test result in an H-type electrolytic cell. The Bi NSs material prepared in Example 1 has a Faraday efficiency of 71.85% at -0.85 V vs. RHE, indicating that it has good selectivity.

[0066] 2) In order to test at a higher current density, a flow electrolyzer was used. In a 1 M KOH solution, the Bi NSs material prepared in the preferred embodiment 1 was used as the cathode, Ag / AgCl was used as the reference electrode, and a Pt sheet was used as the counter electrode. The current density was 50-250 mA cm -2 The electrochemical test was carried out using a Chenhua electrochemical workstation within the current density range, the gas products were detected by gas chromatograph, and the liquid products were detected by nuclear magnetic resonance.

[0067] like Figure 8 As shown, the linear sweep voltammogram under the flow electrolyzer was tested, and the results showed that the BiNSs material prepared in Example 1 had a higher current density and a better CO2 current response in a CO2 environment.

[0068] Draw a graph of the relationship between the total current density and the voltage, such as Fig. 9 As shown, the overall trend is upward.

[0069] In order to test its selectivity at high current density, product detection was carried out, such as Fig.10 As shown, the Bi NSs material prepared in Example 1 is 50-150 mA cm -2 The Faradaic efficiency of formic acid is high in the current density range, especially at 100 mA cm -2 It has a Faraday efficiency of 89.40%, which is comparable to most of the patent levels reported so far, but has a higher current density.

[0070] The partial current density of formic acid is analyzed, such as Fig.11 As shown in the figure, the Bi NSs material prepared in Example 1 has a high conductivity at 100 and 150 mA cm-2 There is a higher formic acid current density when the sample is heated, indicating that it still has a good response to formic acid at a higher current density.

[0071] Energy efficiency can show how efficiently resources are used, e.g. Fig.12 As shown in the figure, the Bi NSs material prepared in Example 1 has a high conductivity at 50 and 100 mA cm -2 Still able to exceed 60% energy efficiency.

[0072] Then at 100 mA cm -2 The stability of the material was tested as follows: Fig.13 As shown, the voltage of the Bi NSs material prepared in Example 1 can still maintain stability within 17 hours.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a bismuth nanosheet material, characterized in that: The following steps are involved: 1) a carbon material is subjected to high temperature calcination treatment and used as a substrate, and a bismuth source is introduced onto the substrate by an electrodeposition method to prepare a precursor BiOI, wherein the electrolyte is a mixed solution containing a bismuth salt and an iodine salt, and the pH range is adjusted to 1-3; 2) The precursor BiOI obtained in step 1) is reduced by an in-situ electro-reduction method to prepare bismuth nanosheet material BiNSs.

2. The method for preparing the bismuth nanosheet material according to claim 1, characterized in that: The carbon material in step 1) is carbon cloth, and the high temperature calcination treatment is calcination at 500-600° C. in a tubular furnace for 90-120 minutes.

3. The method for preparing the bismuth nanosheet material according to claim 1, characterized in that: In step 1), the bismuth salt is Bi(NO3)3·5H2O, and the iodine salt is KI.

4. The method for preparing the bismuth nanosheet material according to claim 1, characterized in that: In step 1), the concentration of bismuth salt in the electrolyte is 0.03-0.05 mol / L, the concentration of iodine salt is 0.3-0.5 mol / L, and the pH is adjusted to 1.

5.

5. The method for preparing the bismuth nanosheet material according to claim 1, characterized in that: The electrodeposition in step 1) was carried out at -0.385 V vs. RHE for 10-12 minutes.

6. The method for preparing the bismuth nanosheet material according to claim 1, characterized in that: The electrolyte for electroreduction in step 2) is KHCO3 with a concentration range of 0.4-0.6 mol / L.

7. The method for preparing the bismuth nanosheet material according to claim 1, characterized in that: The electroreduction in step 2) is carried out at -0.6 V vs. RHE for 3-5 minutes.

8. Bismuth nanosheet material BiNSs prepared by any one of the preparation methods described in claims 1-7.

9. Use of the bismuth nanosheet material as claimed in claim 8 in electrocatalytic reduction of CO2.

10. The bismuth nanosheet material according to claim 8 has a conductivity of 100 mA cm -2 The above is an application of the selective conversion of CO2 into formate.

Citation Information

Patent Citations

  • Bismuth-based catalysts for the electrocatalytic reduction of CO2 to formic acid, their preparation methods and applications

    CN109518222B

  • A bismuth-based composite catalyst for the electroreduction of CO2 to formic acid and its preparation method

    CN109939670B